PENGARUH PELATIHAN DAN MOTIVASI TERHADAP KINERJA DENGAN PENDEKATAN BALANCED SCORECAD - Yumhi Yumhi (Universitas La Tansa Mashiro, 2016)
Based on the results of data and interviews obtained in the field of execution shows the indication has not been implemented optimally the performance of employees of the Secretariat of the General Election Commission of Banten. The authors suspect that has not been implemented optimally the performance is influential with the existence of two factors: training and motivation.In conception the authors apply several theories and concepts related to research variables from some experts such as Ivancevich, Gibson, Fred Luthans, Paul.R Niven, Robert S. Kaplan and David P. Norton and other experts, to explain the effect of variables training and motivation with performance variables.The research method used sequential explanatory method, the data obtained based on observation, interview and answer questionnaire analyzed by statistical correlation technique product moment pearson to know the influence between independent variable that is training and motivation with dependent variable that is performance.In an effort to improve the performance of the staff of the Secretariat of the General Election Commission of Banten, the suggestions of this research are (i) The Election Commission should provide a variety of training so that employees can perform their main tasks and functions with the understanding and objectives desired by their own institutions and communities Banten Province in general. (ii) KPU should give encouragement or encouragement of employees either reward or reward in performing their duties and functions so that employees can socialize to the other employees so that the human resources of employees increases in accordance with the expectations of the organization. (iii) KPU should encourage employees through intensive training that can contribute well to their human resources, so as to support the performance of employees in performing their duties and functions in accordance with the objectives the organization expects